2020
DOI: 10.3389/fcvm.2020.00147
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Injury and Clinical Course of Patients With Coronavirus Disease 2019

Abstract: Background: Cardiac injury is recognized as one of the most common critical complications during exacerbation of coronavirus disease 2019 (COVID-19). This study aimed to investigate the effect of cardiac injury on the clinical course of COVID-19 and to examine its potential mechanism and treatments. Methods and Results: A total of 222 hospitalized patients with COVID-19 from Wuhan were selected for the study during February 10 to March 28, 2020. Demographic, laboratory, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
5
16
0
1
Order By: Relevance
“…Most studies were from China 5 , 9 , 11 , 16 38 ( n = 26), followed by United States 39 43 ( n = 5), Switzerland 44 , 45 ( n = 2), Japan 8 ( n = 1), Korea 46 ( n = 1), Oman 47 ( n = 1), Qatar 48 ( n = 1), Iran 49 ( n = 1), Denmark 50 ( n = 1), Mexico 51 ( n = 1), and Bulgaria 52 ( n = 1). The sample size of included studies ranged from 41 to 5000 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were from China 5 , 9 , 11 , 16 38 ( n = 26), followed by United States 39 43 ( n = 5), Switzerland 44 , 45 ( n = 2), Japan 8 ( n = 1), Korea 46 ( n = 1), Oman 47 ( n = 1), Qatar 48 ( n = 1), Iran 49 ( n = 1), Denmark 50 ( n = 1), Mexico 51 ( n = 1), and Bulgaria 52 ( n = 1). The sample size of included studies ranged from 41 to 5000 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma hs-Tn I concentrations were positively associated with plasma IL-6 concentrations, plasma highsensitivity C-RP concentrations, plasma DD concentrations, and plasma brain natriuretic peptide concentrations [33]. It was demonstrated that for COVID-19 affected persons, in line with higher DD concentrations, high-rise Tn concentration, up to 36 pg/ml on hospital admission were prognostic of decease [33]. It was documented that higher lactate dehydrogenase (LDH), C-RP, and decreased lymphocytes counts were bound with raised death rates in infected persons with COVID-19 [34,35].…”
Section: Zageer Et Almentioning
confidence: 95%
“…It was found that Tn concentrations were associated with concentrations of inflammatory biomarkers [33]. Plasma hs-Tn I concentrations were positively associated with plasma IL-6 concentrations, plasma highsensitivity C-RP concentrations, plasma DD concentrations, and plasma brain natriuretic peptide concentrations [33]. It was demonstrated that for COVID-19 affected persons, in line with higher DD concentrations, high-rise Tn concentration, up to 36 pg/ml on hospital admission were prognostic of decease [33].…”
Section: Zageer Et Almentioning
confidence: 98%
See 1 more Smart Citation
“…SARS-CoV-2 infection mainly affects the respiratory tract 11 but recently has been associated with significant multiple organ dysfunction syndrome. 12 One of the most common critical complications during COVID-19 is myocardial injury, 13 , 14 especially in patients with a higher inflammatory profile. 13 …”
Section: Introductionmentioning
confidence: 99%